Tinjauan Yuridis Sistem First To File Terhadap Pendaftaran Merek Citayam Fashion Week Menurut Undang-Undang Nomor 20 Tahun 2016 Tentang Merek Dan Indikasi Geografis. - Rodrigo, Valencia; Abbon, Thomas; Panjaitan, Edward M.L (Fakultas Hukum Universitas Kristen Indonesia, 2024)
The registration of Citayam Fashion Week trademark rights in mid-2022 by famous artist Baim Wong triggered a public reaction that considered him as immoral, because it was considered that he was not the one who popularized the Citayam Fashion Week brand. The purpose of this article is to examine who is entitled to the Citayam Fashion Week trademark according to law number 20 of 2016 concerning trademarks and geographical indications,and whether the registration made by Baim Wong has been in accordance with the provisions of the first to file system stipulated in the Trademark Law. The results of the this article are based on the Trademark Act, the subject entitled to the trademark is the subject who first registered the trademark rights to the Ministry of law and human rights without violating the provisions of the trademark can not be registered and the trademark must be rejected. Baim Wong's actions in registering the Citayam Fashion Week trademark are in accordance with the provisions of the first registrant system or First to file, and do not violate the provisions of the trademark cannot be registered and rejected as stipulated in Law Number 20 of 2016 Trademarks and Geographical Indications, and therefore although Baim Wong is morally unfit but because the trademark law does not recognize the term moral, then Baim Wong is entitled to register the Citayam Fashion Week trademark.